(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Dental implantation remains a promising and widely used method for the treatment of dentition defects, effectively restoring the functions of the dentoalveolar system and correcting facial aesthetic deficiencies. Objective: To evaluate the effectiveness of guided tissue regeneration using platelet-rich plasma (PRP) in patients with partial secondary edentulism. Materials and Methods: In accordance with the study objectives, 50 patients diagnosed with “Partial secondary edentulism of the maxilla” were examined. All patients were divided into two groups: Group 1 (Main group): 25 patients aged 21–36 years with bone deficiency confirmed by radiological examination, treated using guided bone regeneration (GBR) with platelet-rich plasma. Group 2 (Comparison group): 25 patients aged 25–45 years with bone deficiency confirmed radiographically, treated using conventional guided bone regeneration techniques. Research methods included clinical, radiological, and statistical analyses. Results: Preoperative computed tomography (CT) revealed pronounced bone atrophy (2.2–3.6 mm in width) in all patients of the main group, while bone height was sufficient (11.0–15 mm). Preoperative bone mineral density was assessed in all patients. Six months after guided bone regeneration, CT scans demonstrated increased alveolar ridge dimensions and bone density in the main group. Implant osseointegration one year after placement reached 100%. The total duration of surgical treatment in the main group before initiation of prosthetic rehabilitation was 12 ± 0.5 months. Conclusions: Comparative CT analysis demonstrated that six months after GBR with PRP, bone density increased on average by 22.7% in women and 21.4% in men. In contrast, after conventional GBR, bone density in the maxilla decreased by an average of 3.8% in women and 2.4% in men.